Analysis of Abalone Business Development in Maluku through Human Resource Development and Optimization Marketing Strategy - Latuihamallo, Juliana; Atamimi, Rachma; Rehatta, Pieter N. R. (International Journal of Psychosocial Rehabilitation, 2020)
This research aimed to develop abalone businesses in Maluku through human resource development and opimizing marketing strategies and from business actors. The abalone business development is based on fishbone analysis to find out policies that provide more optimal results to identify optimization both with marketing and human resource development. Meanwhile, the Analysis Hierarchy Process (AHP) was used aiming to get the right strategy for fishermen or collectors/buyers. The study results show that the government has a more important role than other parties.